Pain Complaints in Patients with Urinary Catheterization in the Emergency Room - Qamarya, Nurul; Rukayah, Siti; Fajar Cahya, Mochamad Robby; Tondok, Santalia Banne; Nasution, Revie Fitria; Dardi, Satriana; Fredy, Khalid; Pannyiwi, Rahmat (Institute of Accounting Research and Novation (IARN), 2023)
Urine retention is an emergency that must get immediate help / action, because total urine retention that lasts several days can result in urosepsis which can end in death, so it needs rapid management by catheterization. Comparing the effectiveness of jelly administration techniques applied to the tip of the catheter and jelly sprayed directly at the urethral meatus on pain complaints in patients with urinary catheterization. The type of research used is a quasy experiment, the sample is taken with purposive sampling technique, this study seeks to reveal the causal relationship of the dependent and independent variables with measurements after the intervention.